Little dinosaur - Wilson, Trevor; Forss, Ian (SRA Macmillan/McGraw-Hill Columbus, Ohio, 1995)
Unhappy because he is so small, a young dinosaur follows the suggestions of larger dinosaurs, but only the admiration of a baby makes him feel better about himself